A Mathematical Model for Iraqi Airways Company about Evaluating Its Objectives and Strategies - Abbas, Jabbar; Ouda , Eman Hassan; Fahmi , Imad Noah Ahmed (Iraqi Journal of Science, 2022)
In this paper, we introduced a mathematical model for Iraqi Airways Company about evaluating its objectives and strategies. First, we studied Iraqi Airways schedules with different departure cities for each airline path. Then, we applied some fuzzy integrals for determining the best airline path.